Film and Pore Diffusion Modeling for Adsorption of Reactive Red 2 from Aqueous Solution on to Activated Carbon Preparedfrom Bio-Diesel Industrial Waste. Issue Volume 7:Issue S1(2010) (2010) - Karthikeyan, S.; Sivakumar, B.; Sivakumar, N.
Abstract : The bio-diesel industrial waste, Pongamia pinnata seed shell was utilized as a potential adsorbent for the toxic textile dye 'Reactive Red 2'. Preliminary information was gathered by batch mode contact time adsorption studies, which include effect of pH, contact time, dye concentration and temperature. Plausible mechanism of the on going adsorption process and thermodynamic parameters involved were obtained by carrying out kinetic measurements. To identify whether the on going process is particle diffusion or film diffusion, the treatment given by Boyd and Reichenberg was employed.